Mengintegrasikan Ilmu Modern Dengan Nilai Keislaman: Pendekatan Interdisipliner Dalam Pendidikan Islam - Retnowati, Endang; Hatni, Hatni; Amril, Amril; Dewi, Eva (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
The interdisciplinary approach to Islamic education offers an innovative way to combine modern science with Islamic values. This study examines how the combination of current science and Islamic principles can contribute to the development of a more comprehensive and relevant curriculum. Using qualitative analysis methods, this study identifies practical strategies to bring the two fields together effectively. The findings of the study show that an interdisciplinary approach not only deepens academic understanding, but also strengthens the moral and ethical aspects of education. This research is expected to provide a new perspective for educators and policymakers in designing educational programs that balance modern knowledge and authentic Islamic teachings.